Advances in cyanogenic glycosides biosynthesis and analyses in plants : a review - Ganjewala, Deepak (Acta Biologica Szegediensis, 2010)
A number of species of plants produce repertoire of cyanogenic glycosides via a common biosynthetic scheme. Cyanogenic glycosides play pivotal roles in organization of chemical defense system in plants and in plant–insect interactions. Several commercial crop plants such as sorghum (Sorghum bicolor), cassava (Manihot esculenta) and barley (Hordium vulgare) are cyanogenic and accumulate significant amounts of cyanogenic glycosides. The study of biosynthesis of dhurrin in sorghum has underpinned several early breakthroughs in cyanogenic glycoside researches. Despite great deal of structural diversity in cyanogenic glycosides, almost all of them are believed to be derived from only six different amino acids L-valine, L-isoleucine, L-leucine, L-phenylalanine, or L-tyrosine and cyclopentenyl-glycine (a non protein amino acid). Our knowledge about biosynthesis of cyanogenic glycosides and molecular regulatory processes underlying their biosynthesis has been increased impressively in the past few years. The rapid identification, characterization and cloning of genes encoding enzymes of the cyanogenic glycoside biosynthetic and catabolic pathways from several plants has greatly facilitated our understanding of cyanogenic glycosides biosynthesis and regulation. Today it is known that enzymes of cyanogenic glycoside biosynthetic pathway in sorghum are organized as metabolon most likely to those of other secondary metabolic pathways. Knowledge of state of art of biosynthesis and regulation of cyanogenic glycosides made possible the metabolic engineering of these pathways resulting in development of transgenics of cassava, tobacco, lotus and Arabidopsis with manipulated cyanogenic glycosides content. Simultaneously, many new developments have been witnessed in methods/techniques/ procedures for detection of cyanogenic glycosides in plant samples, foods and foodstuffs. The present review sequentially discusses all of these issues with updated information gathered from the published reports on cyanogenic glycosides.